2022
DOI: 10.1080/10717544.2022.2075987
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapeutic effect of transformable peptides containing pheophorbide a on colorectal cancer

Abstract: Photodynamic therapy (PDT) and photothermal therapy (PTT) have attracted research interest for their noninvasive nature and selective treatment of tumor tissues. They are effective through the generation of reactive oxygen species (ROS) or heat. Nevertheless, several problems, including low bioavailability and long-lasting cutaneous photosensitivity, have limited their clinical application. In this study, we reported an in situ self-assembly strategy that could improve various biological properties of the phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…[174][175][176][177][178] Some examples of such combination therapies include unitary combinations from individual therapeutic modality, binary combinations of phototherapy, chemotherapy, radiotherapy, and immunotherapy, as well as ternary or even more combinations. [179][180][181][182] In terms of binary combination therapy, our group reported an reactive morphological transformation of the peptide scaffold DPEIM for implementing photodynamic and chemodrug combination cancer therapy (Fig. 8).…”
Section: Combination Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…[174][175][176][177][178] Some examples of such combination therapies include unitary combinations from individual therapeutic modality, binary combinations of phototherapy, chemotherapy, radiotherapy, and immunotherapy, as well as ternary or even more combinations. [179][180][181][182] In terms of binary combination therapy, our group reported an reactive morphological transformation of the peptide scaffold DPEIM for implementing photodynamic and chemodrug combination cancer therapy (Fig. 8).…”
Section: Combination Therapymentioning
confidence: 99%
“…174–178 Some examples of such combination therapies include unitary combinations from individual therapeutic modality, binary combinations of phototherapy, chemotherapy, radiotherapy, and immunotherapy, as well as ternary or even more combinations. 179–182…”
Section: Peptide Assembly In Living Cells For Disease Therapymentioning
confidence: 99%
“…81,155,156 In addition to increasing size, shape transformation from nanospheres to nanofibers can also help to overcome intratumoral pressure and enhance tumor retention. 157,158 Nevertheless, a single transformation from nanospheres to large nanofibers might leave nanodrugs lingering around the edge of solid tumors, 103,108 thus hindering the deep tumor penetration. With these concerns, a dually responsive nanotransformer with shape and size transformations was introduced by Jia et al 159 In detail, in the acidic pH tumor stroma, particles with a size of 50 nm could undergo a transition from nanospheres to nanofibers to enhance the tumor retention.…”
Section: Intertumoral Pressurementioning
confidence: 99%
“…Recent studies have shown that aggregate formation can significantly enhance the photothermal conversion efficiency of photosensitizers, as close stacking leads to fluorescence quenching and intersystem crossing, which facilitates energy dissipation through nonradiative relaxation. , Leveraging this phenomenon, researchers have innovatively combined peptides with photosensitizers to create conjugate materials that serve as nanotheranostics for PTT. , These conjugates excel in biocompatibility and degradability, and offer the flexibility of structural design. The strategic design of peptide-photosensitizer conjugates allows for the formation of nanostructures that can self-assemble into well-defined aggregates, which not only improve PTT efficiency but also may exploit the tumor-targeting enhanced permeability and retention (EPR) effect. , For example, Zou et al. reported the fabrication of a peptide-porphyrin conjugate to form photothermal nanodots with highly efficient light-to-heat energy conversion for effective tumor accumulation and ablation with little side effect .…”
Section: Introductionmentioning
confidence: 99%